Local ecological knowledge of coffee agroforestry farmers on earthworms and their relation to soil quality in East Java (Indonesia) - MILA OKTAVIA MARDIANI; IRMA ARDI KUSUMAWATI; EKA PURNAMASARI; CAHYO PRAYOGO; MEINE VAN NOORDWIJK; KURNIATUN HAIRIAH (Society for Indonesian Biodiversity, 2022)
Abstract. Mardiani MO, Kusumawati IA, Purnamasari E, Prayogo C, van Noordwijk V, Hairiah K. 2022. Local ecological knowledge of coffee agroforestry farmers on earthworms and their relation to soil quality in East Java (Indonesia). Biodiversitas 23: 3344-3354. Farmers manage their land-based on their understanding of biotic and abiotic factors, including soils, and how these factors affect crop growth and productivity. Their local ecological knowledge (LEK) is built upon intergenerational transfer and can use concepts that don’t directly match those of current science-based ecological knowledge. We explored farmer LEK related to soil organic matter management and earthworms in coffee-based agroforestry systems on volcanic slopes in East Java (Indonesia) by in-depth interviews with key informants and by surveying the concurrence of respondents, stratified by gender and age, with resulting statements. The term used in the local language for earthworms (‘cacing tanah’) included a range of species. According to 22% (n=48) of farmers, small earthworms (probably Pontoscolex corethrurus) are harmful to coffee trees because they eat the roots. Also, 54% (n=48) of farmers thought earthworms that eat soil cause a decrease in soil volume. However, according to the farmers, large earthworms (reddish-brown) can fertilize the soil by leaving their casts on the soil surface. Such worms are often found in coffee agroforestry systems. Farmers have little explicit knowledge of the activities of earthworms and their relation with litter as a source of food. Farmer knowledge of ecosystem services provided by earthworms can enrich current scientific literature and trigger a two-way dialogue.